Osteoblast Differentiation of Human Dental Pulp Stem Cells with Dexamethasone in-situ Forming Implant - Zahra Tayarani-Najaran; Hossein Kamali; Farzin Hadizadeh; Farahnaz Ahmadi; Sahar Shahidi; elham khodaverdi (Mashhad University of Medical Sciences, 2021)
Introduction: Dental pulp stem cells (DPSCs) are known as multipotent stem cells which differentiate into three different cell lines, including osteocytes, chondrocytes, and adipocytes. Until now, dental precursor cells have been used in tissue engineering studies for pre-clinical applications. The dexamethasone in-situ forming implant (ISFI) is capable of releasing medicine that is trapped in the aquatic environment slowly and continuously in a few days to weeks. The present research aimed to investigate the ability of human DPSCs to differentiate into bone tissue in the presence of dexamethasone ISFI as a source of dental mesenchymal stem cells. Materials and Methods: The DPSCs were extracted from the third molar tooth. To investigate the process of differentiation into osteoblasts, β-glycerophosphate, ascorbic acid, and dexamethasone ISFI in solution were added to the cells. The differentiation process was verified by Alizarin Red S stain, alkaline phosphatase activity (ALP), and western blot technique. Results: Based on the results of Alizarin Red S staining, extracellular matrix mineralization was increased in dexamethasone ISFI (i.e., implant) and standard (i.e., dexamethasone) groups. In addition, the ALP activity underwent an increase in these groups, compared to the related control group. Furthermore, the protein level of ALP,osteopontin, and runt-related transcription factor two increased in the group treated with dexamethasone ISFI, compared to the control group. Conclusion: Findings of this study indicated that dexamethasone ISFI could increase the process of differentiation of DPSCs into osteoblasts.